The effect of nano-Macro elements (NPK) and Amino Spray on some Physical and Chemical Characteristics of date palm fruits ( Phoenix dactylifera L. ) Al-Sayer cultivar. - Rashid Saqr, Asma Rashid Saqr; AL-zubaidy, Batool Hanoon Falih (University of Thi-Qar Journal of agricultural research, 2024)
This experiment was carried out during the growing season (2023 AD) in one of the private orchards in Thi Qar Governorate, with the aim of studying the effect of spraying fruits with concentrations of the nano-macro elements NPK (0, 75, and 150) mg L-1 and Amino Spray with concentrations (0, 2, and 4) ml L-1 and their interactions in some physical and chemical characteristics of the fruits of the Al-Sayer cultivar at the Rutab stage. The results showed the significant superiority of the nano-macro elements NPK at a concentration of (150 mg L-1), recording the highest averages in both the weight of the fruit and the core (9.322 and 8.453) g, respectively , and the concentrations of nitrogen, phosphorus and potassium (2.60, 0.40 and 2.783). ) % respectively . The spraying treatment with Amino Spray at a concentration of(4 ml L-1) was significantly superior in increasing the averages of both the weight of the fruit and the core (8.483 and 7.678 ) g , respectively, and the percentages of nitrogen, phosphorus and potassium (2.76, 0.43, and 963.3) % , respectively .